Relative Performance Feedback to Teams - William Gilje Gjedrem; Ola Kvaløy (Center for Economic Studies and ifo Institute (CESifo), 2018)
Between and within firms, work teams compete against each other and receive feedback on how well their team is performing relative to their benchmarks. In this paper we investigate experimentally how teams respond to relative performance feedback (RPF) at team level. We find that when subjects work under team incentives, then RPF on team performance increases the teams' average performance by almost 10 percent. The treatment effect is driven by higher top performance, as this is almost 20% higher when the teams receive RPF compared to when the teams only receive absolute performance feedback (APF). The experiment suggests that top performers are particularly motivated by the combination of team incentives and team RPF. In fact, team incentives motivate significantly higher top performance than individual incentives when the team is exposed to RPF. We also find notable gender differences. Females respond negatively to individual RPF, but even more positively than males to team RPF.
Keywords: C91; M50; M52; 330; teams; performance feedback; performance pay; experiment